Adenosine 5'-monophosphate-stimulated cyanide-insensitive respiration in mitochondria of Moniliella tomentosa. - Hanssens, L (1976)
Mitochondria of the yeastlike fungus Moniliella tomentosa oxidize reduced nicotinamide adenine dinucleotide, reduced nicotinamide adenine dinucleotide phosphate, succinate, isocitrate, and lactate. These oxidations are completely inhibited by cyanide or antimycin A in mitochondria isolated from cells grown in the standard medium. On the other hand, the oxidation of all substrates, except lactate, is almost completely insensitive to cyanide or antimycin A in mitochondria from cells grown in the presence of ethidium bromide. In this instance, the oxidation is mainly mediated by an alternate oxidase which can be blocked by salicyl hydroxamic acid. The alternate oxidase can be specifically stimulated by adenosine 5'-monophosphate and this provides a new method for the characterization of the alternate oxidase in mitochondria of M. tomentosa.